Pengembangan Budaya dan Iklim Kampus yang Sehat Melalui Kegiatan Kemanusian - Kartika Sari Lubis; Edi Winata; Siti Syahsudarmi (Jurnal Pengabdian Masyarakat Eka Prasetya, 2023)
By engaging in humanitarian activities through blood donation, campuses can serve as positive agents of social change and make significant contributions to society. In addition to assisting those in need of blood, the involvement of campuses in blood donation activities can also build their reputation as institutions that care and are responsible for the general welfare. Sukma College of Management (STIM) has established partnerships with humanitarian institutions or organizations such as the Indonesian Red Cross (PMI) that are involved in blood donation activities. Through this collaboration, campuses can make even greater contributions to helping the community and act as agents of change on a broader scale.